Races of the wheat stem rust fungus in Brazil, from 1982 to 1985 - Coelho, Elisa T.; Sartori, João F. (Pesquisa Agropecuaria Brasileira, 2014)
From 1982 to 1985, 652 samples of the wheat stem rust fungus (Puccinia graminis E. sp. tritici) were collected in the Brazilian wheat regions and in some other countries of South America. The race G17 was predominant in 1982 and 1983, constituting more than 50% at the isolates identified. Race G19 and G20 composed about 17% in 1982 and race G20 about 22% in 1983. In 1984, races G17, G19 and G20 were prevalent in about 25% each. In 1985, races G15, G17 and G19 presented a frequency of about 20% each. During 1982-1983, four new races were identified: G21, isolated from Patos de Minas, MG, and Londrina. PR, in 1983; G22 from Palotina, PR, Dourados, MS and São Borja, RS; G23 from Piratini, RS in 1984, and G24 from Cruz Alta, RS and Londrina, PR in 1985. Considering the occurring races in the sampled areas, the genes Sr 22, Sr 24, Sr 25, Sr 26, Sr 27, Sr 31 and Sr 32, confer, isolately, resistance to all races of Puccinia graminis tritici.
Keywords: Puccini graminis f. sp. tritici; genes of resistance; formulas of virulence.